PENDETEKSIAN MANAJEMEN LABA RIIL DI INDONESIA (Studi Empiris pada Perusahaan yang Melakukan Right Issue Antara Tahun 2011-2015 Dan Terdaftar Di BEI) - Christyansah, Galih Ivan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims is to detect the earnings management through manipulation of real activity in the company that plans to offer additional shares rights issue. Earnings management is measured using three proxies manipulation of real activity, namely the activity of cash flow operating activities, costs of production, and through discretionary costs. Real activity manipulation model that used in this study is based on the Roychowdhury’s model (2006).The data used in this research is secondary data in the form of financial statements. The population in this study are all companies listed on the Indonesia Stock Exchange by using samples selected through purposive sampling method. Regression analysis was used to find the abnormal value estimate of operating cash flow, production costs, and discretionary costs. The results showed that company was not indicated to use real earnings management activity by lowering the operating cash flow, raising production costs, and lower discretionary costs. The Company is not indicated to use real earnings management activity can be caused the management of companies prefer to use accrual earnings management activity.Keywords: Earnings management, real activities manipulation, right issue